Associations between tissue‐based CD3+ T‐lymphocyte count and colorectal cancer survival in a prospective cohort of older women. Issue 1 (17th November 2020) - Oyenuga, Mosunmoluwa; Vierkant, Robert A.; Lynch, Charles F.; Pengo, Thomas; Tillmans, Lori S.; Cerhan, James R.; Church, Timothy R.; Lazovich, DeAnn; Anderson, Kristin E.; Limburg, Paul J.; Prizment, Anna E.
Abstract: Tumor‐infiltrating lymphocytes in colorectal cancer (CRC) predict better survival. However, associations between T‐lymphocyte count in histologically normal tissues from patients with CRC and survival remain uncertain. We examined associations of CD3+ T‐cells in colorectal tumor and histologically normal tissues with CRC‐specific and all‐cause mortality in the prospective Iowa Women's Health Study. Tissue microarrays were constructed using paraffin‐embedded colorectal tissue samples from 464 women with tumor tissues and 314 women with histologically normal tissues (55–69 years at baseline) diagnosed with incident CRC from 1986 to 2002 and followed through 2014 (median follow‐up 20.5 years). Three tumor and two histologically normal tissue cores for each patient were immunostained using CD3+ antibody and quantified, and the counts were averaged across the cores in each tissue. Cox proportional hazards regression estimated hazard ratios (HR) and 95% confidence interval (CI) for CRC‐specific and all‐cause mortality. After adjustment for age at diagnosis, body mass index, smoking status, tumor grade, and stage, HRs (95% CI) for the highest versus lowest tertile of tumor CD3+ score were 0.59 (0.38–0.89) for CRC‐specific mortality and 0.82 (0.63–1.05) for all‐cause mortality; for histologically normal CD3+ score, the corresponding HRs (95% CI) were 0.47 (0.19–1.17) and 0.50 (0.27–0.90), respectively. The CD3+ score combining the tumor and histologically normal scores was inversely associated with CRC‐specific and all‐cause mortality. Although the association between tumor CD3+ score and all‐cause mortality was not significant, both higher CD3+ T‐lymphocyte counts in tumor and histologically normal scores tended to be associated with lower CRC‐specific and all‐cause mortality.